2020
DOI: 10.1159/000506116
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Stroke Patients: Are There Sex Differences?

Abstract: Background: We aimed to examine sex differences in symptom characteristics and pharmacological responses in post-stroke depressive (PSD) symptoms. Methods: This is a post hoc analysis of EMOTION (ClinicalTrials.gov, NCT01278498), a randomized, placebo-controlled, double-blind trial that examined the efficacy of escitalopram for 3 months on depression in patients with acute stroke. Depressive symptoms were evaluated using the 10-item Montgomery-Åsberg Depression Rating Scale (MADRS). Baseline characteristics, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…This antioxidant and anti-in ammatory action could, at least in part, justify the results found in the present study. Interestingly, a clinical study with individual with post-stroke depressive symptoms evidenced that treatment responses of escitalopram tended to be more pronounced in the female group, suggesting different responses according to sex, going according to the data observed in the present study (Lee et al 2020). Moreover, after review 15 randomized, placebo-controlled trials, Khan et al (2005) observed that women had a signi cantly greater response than men to SSRI antidepressants (Khan et al 2005).…”
Section: Discussionsupporting
confidence: 84%
“…This antioxidant and anti-in ammatory action could, at least in part, justify the results found in the present study. Interestingly, a clinical study with individual with post-stroke depressive symptoms evidenced that treatment responses of escitalopram tended to be more pronounced in the female group, suggesting different responses according to sex, going according to the data observed in the present study (Lee et al 2020). Moreover, after review 15 randomized, placebo-controlled trials, Khan et al (2005) observed that women had a signi cantly greater response than men to SSRI antidepressants (Khan et al 2005).…”
Section: Discussionsupporting
confidence: 84%
“…The significantly higher prevalence of PSDS in women than men in bivariate analyses (38.6% women vs 26.6% men, P < .001) aligns with some but not all studies 21 , 22 , 25 , 26 , 48 , 49. Furthermore, in the same CR program using the same depression screening tool, this primary finding was similar to that of cardiac patients except that the proportion with depressive symptoms was lower for both women and men with cardiac disease (30.2 vs 19.3%, P < .001) 27…”
Section: Discussionsupporting
confidence: 76%
“…PSD usually presents during two ranges after stroke: one between 3-6 months and the other between 2-3 years after stroke [118]. With the same clinical manifestations of traditional depression, PSD is mainly characterized by mood dysfunctions including depressive feelings, indifference, irritability, and vegetative signs including sleep disorders [119,120]. Despite the similarity to other depressed patients with atherosclerotic diseases, the symptoms of depression were more severe in patients with PSD than in those with atherosclerotic diseases [121].…”
Section: Sleep Disorders and Post-stroke Depression (Psd)mentioning
confidence: 99%